Proceedings of the 14th ACM International Conference on Information and Knowledge Management 2005
DOI: 10.1145/1099554.1099747
|View full text |Cite
|
Sign up to set email alerts
|

Implicit user modeling for personalized search

Abstract: Information retrieval systems (e.g., web search engines) are critical for overcoming information overload. A major deficiency of existing retrieval systems is that they generally lack user modeling and are not adaptive to individual users, resulting in inherently non-optimal retrieval performance. For example, a tourist and a programmer may use the same word "java" to search for different information, but the current search systems would return the same results. In this paper, we study how to infer a user's in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
226
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(228 citation statements)
references
References 22 publications
0
226
0
2
Order By: Relevance
“…This is observed by Shen et al [156] where it is reported that the performance improvement is more substantial for precision at the top 20 documents than for precision at the top 10 documents. The authors' explanation for this difference between precision at ten and precision at twenty is that after twenty browsed documents the user accumulates more interaction with the system, thus letting the system to calculate better estimations than after ten documents.…”
Section: Using Click-through Datamentioning
confidence: 59%
See 3 more Smart Citations
“…This is observed by Shen et al [156] where it is reported that the performance improvement is more substantial for precision at the top 20 documents than for precision at the top 10 documents. The authors' explanation for this difference between precision at ten and precision at twenty is that after twenty browsed documents the user accumulates more interaction with the system, thus letting the system to calculate better estimations than after ten documents.…”
Section: Using Click-through Datamentioning
confidence: 59%
“…So far there is nothing personalized because the user's actions are not labeled by the user. Instead of labeling every user action, Shen et al [156] propose injecting a user's mathematical model chosen from a fixed set of user's models. The goal is to minimize a risk function of the user's actions, the system's past responses and the user's model.…”
Section: Using Query Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, we provided algorithms for computing naming functions appropriate for systems that are based on the vector space model. Somehow related work includes [4,7,1].…”
Section: Discussionmentioning
confidence: 99%